2022
DOI: 10.3389/fpsyg.2022.996144
|View full text |Cite
|
Sign up to set email alerts
|

The associations among athlete gratitude, athlete engagement, athlete burnout: A cross-lagged study in China

Abstract: The purpose of this study is to explore the causal relationship among athlete gratitude, athlete engagement, athlete burnout by cross-lag analysis of longitudinal associations. Two questionnaire surveys were conducted on 352 Chinese athletes with an interval of 1 year using gratitude questionnaire, athlete engagement questionnaire and athlete burnout questionnaire. The analysis yielded four main findings. (1) The overall level of athlete gratitude and athlete engagement was high in China. Chinese athletes at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…ABQ scores at baseline are at a medium level, consistent with a previous study conducted on elite athletes which are around 2.67. [ 26 ] Hough et al . [ 35 ] reported that subjects` fatigue and burnout scores were higher after a cycling training period, which is the opposite in the present study that the mean scores of the EPE, RSA, SDE, and total ABQ were slightly decreased after YPP, indicating YPP might prevent athletes from burnout and even improve it if prolonging the intervention period or applying a more integrated approach of yoga practices (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABQ scores at baseline are at a medium level, consistent with a previous study conducted on elite athletes which are around 2.67. [ 26 ] Hough et al . [ 35 ] reported that subjects` fatigue and burnout scores were higher after a cycling training period, which is the opposite in the present study that the mean scores of the EPE, RSA, SDE, and total ABQ were slightly decreased after YPP, indicating YPP might prevent athletes from burnout and even improve it if prolonging the intervention period or applying a more integrated approach of yoga practices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we adopted the formula of athlete burnout weighted total score established by Liancheng and Liwei[ 25 ] (S weighted total score = S emotional/physical exhaustion × 0.21 + S reduced sense of accomplishment × 0.47 + S sport devaluation × 0.32) to calculate the athlete burnout total score. [ 26 ] All measures were gathered before and after 1 day of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“… Seligman and Csikszentmihalyi (2014) proposed the concept of positive psychology, applying interventions to increase positive feelings, at the end of the 20th century. With the rise of positive psychology, gratitude has gradually become an important research topic ( Guo et al, 2022 ). Gratitude refers to the psychological tendency to understand or respond the help of others with appreciative emotions and behaviors ( McCullough et al, 2002 ).…”
Section: What Is Gratitude?mentioning
confidence: 99%
“…Existing research on athlete engagement primarily adopts perspectives from work engagement, with verified antecedent variables such as motivation [ 6 ], gratitude [ 7 ], coping style [ 8 ], social support [ 9 , 10 ], understanding care [ 11 ], and coaches’ leadership behavior [ 12 ]. Among the individual factors, motivation has the most significant influence [ 13 – 15 ], wheres social support holds the most important role among environmental factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%